2012
DOI: 10.1007/s11250-012-0235-9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of controlling contagious bovine pleuropneumonia in sub-Saharan Africa

Abstract: Contagious bovine pleuropneumonia (CBPP) is a disease of economic importance that is widely distributed in sub-Saharan African and contributes significantly to cattle morbidity and mortality. Control of CBPP offers a number of challenges as a result many developing countries in Africa are still struggling with this disease. In this study, we look at the challenges encountered in CBPP control in sub-Saharan Africa from the Zambian perspective. In conducting this study, we reviewed scientific literature and repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…A similar situation seems to obtain in Ghana where Opare [9] indicated that high levels of knowledge about vaccination had not been actualised into practices by farmers in Tamale Municipality. Equally, a review of challenges faced by sub-Saharan countries in controlling CBPP disease in Western province identified failure of veterinary services as one major challenge expressed by most staff who were involved in the control [17]. Likewise, in a review paper by Siamudaala et al (2006), inadequate technical and administrative support, erratic funding and supply of logistics were cited as major constraints of anthrax control in Zambia [1].…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation seems to obtain in Ghana where Opare [9] indicated that high levels of knowledge about vaccination had not been actualised into practices by farmers in Tamale Municipality. Equally, a review of challenges faced by sub-Saharan countries in controlling CBPP disease in Western province identified failure of veterinary services as one major challenge expressed by most staff who were involved in the control [17]. Likewise, in a review paper by Siamudaala et al (2006), inadequate technical and administrative support, erratic funding and supply of logistics were cited as major constraints of anthrax control in Zambia [1].…”
Section: Discussionmentioning
confidence: 99%
“…Commercial beef farmers are defined as farmers who own large herds of mostly exotic breeds of cattle and contribute the remaining 16% (Sinkala et al 2014). Commercial beef farms are mostly situated along rail lines on large pieces of titled land, while traditional beef farmers are scattered in rural areas, often practising communal grazing on land held in trust by traditional leaders (Muma et al 2011;Muuka et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Challenges exist in controlling movement in the traditional sector due to communal grazing, transhumance, use of oxen for transport, hiring of bulls for mating, and other vices like shifting from village to village; mafisa and lobola [66]. The immunological diversity in prevalent serotypes and topotypes that exist in Zambia may render FMD difficult to control in present circumstances [67, 68].…”
Section: Challenges Of Controlling Fmd In Zambiamentioning
confidence: 99%
“…This is despite movement of wildlife and livestock within and between ecosystems including transborder movement being rife. Previously, game fences were erected in 1950s to control movement of tsetse flies from wildlife to cattle around the Kafue national park until the 1980s when they collapsed because they could not be maintained [66]. The effectiveness of these fences in controlling FMD is questionable given that outbreaks were recorded during the period.…”
Section: Challenges Of Controlling Fmd In Zambiamentioning
confidence: 99%
See 1 more Smart Citation